Children are Lived Social Difficulties and their Coping Strategies of Using the Program ‘Zippy’s Friends’ in Elementary School Adaptation Period: the Parents’ Attitude - Rimkevičienė, Violeta; Mauragienė, Vijolė (Pedagogika, 2016)
The present article discusses the results of the research on parents’ attitudes towards their children-experienced difficulties analysed within the framework of the international ‘Zippy’s Friends’ Programme at the adaptation period in school. The findings of the research obtained on the basis of parents’ answers allow to assert that ‘Zippy’s Friends’ Programme was highly effective in assisting children at school to go through the period of adaptation and to overcome difficulties. The emotional states of the children who participated in the Programme improved considerably, and it took the children a shorter time to get used to school requirements. The research findings revealed that parents observed their children’s active attempts made at solving independently the arising problems or turning for help to others, or providing help to their peers; the children who participated in the Programme were more ready to show initiative, they felt more confident and were willing to demonstrante their abilities in solving problems of adaptation at school. The results of the research provided sufficient evidence in favour of these positive changes. The children who were Programme participants proved more capable of adjusting to the overall school environment, consequently, they experienced fewer problems of discipline and self-regulation, and, thus, their learning achievements were higher as well. In this way, ‘Zippy’s Friends’ Programme proved as a very effective instrument in helping children to acquire higher adaptive skills needed to function successfully both emotionally and socially in the new to children school environment. The article presents the results of the study of parental attitudes towards children lived difficulties through an international program ‘Zippy’s Friends’, an adaptation of the school term. The analysis of the parents found out that the program ‘Zippy’s Friends’ helped the children to adapt to school, to overcome their difficulties. Participated in the survey overall emotional well-being is better, easier to become accustomed to the school’s procedures. The analysis of the results showed that parents of children observed tests to actively solve problems, seek help, to try to help friends, themselves often showed initiative, independence and skills in solving problems in the adaptation of the school term. Children participating in the program ‘Zippy’s Friends’ often tried to help others overcome difficulties, to successfully overcome the problems. The results showed that children who participated in the program ‘Zippy’s Friends’ is better adapted in school life than the control group children. The results showed that ‘Zippy’s Friends’ “children had fewer problems with self-regulation, learning and discipline, and they are used much more different coping strategies than children in the control group. In general, the results show that the children who had participated in the ‘Zippy’s Friends’ program received higher behavioral and emotional adaptation to school evaluations and divorced more positive reactions to the new school environment”.